Peningkatan Keterampilan Santriwati Pesantren Nurul Qadim Dalam Pembuatan Sabun Cuci Piring Alami - Salsabillah, Windhy Mutiara; Az-Zahra, Kamila; Fitri, Nana Roudlotul; Sudarto, Novadana Salsabillah Putri; Widyana, Azizah; Hayati, Kinanti Resmi (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2025)
This Real Work Lecture activity aims to develop the skills of female students at the Nurul Qadim Islamic Boarding School in making natural dishwashing soap as part of efforts to develop skills in making natural dishwashing soap which is not only effective but also enjoyable and beneficial for skin health, and supports lifestyle. which is more environmentally friendly. This natural dish soap is designed to replace commercial products which often contain harsh chemicals and can have a negative impact on health and the environment. This training was carried out for 3 days using counseling methods and direct practice which was carried out on 02 - 04 August 2024. A total of 20 female students were involved in this training, which included theory about the definition of dishwashing soap, the natural ingredients used, the manufacturing process, soap testing, and the ecological benefits of eco-friendly products. This success proves the effectiveness of the training in improving practical skills, increasing knowledge, and building the self-confidence of female students, in this case showing that 90% of participants succeeded in following the soap training well and showed a great understanding of the soap making process. The conclusion of this activity is that this training not only improves the practical skills of female students but also instills awareness about environmental sustainability.